Diagnostic Potential of Salivary Interleukin-1β and IL-10 for Distinguishing Periodontal Health From Periodontitis and Stable From Unstable Periodontitis: A Case–Control Study - Zainab J. Raheem; Hayder Raad Abdulbaqi (International Journal of Dentistry)
Conclusion: Salivary IL-1β, IL-10, and IL-1β/IL-10 have a high potential to discriminate healthy control from periodontitis and stable from unstable periodontitis.